A new learning experience: voluntary preparatory course for the bachelor's degree in engineering - Muriel Botey; Olga Alcaraz (OmniaScience, 2012)
This paper reports on a new experience carried out at school associated with the Technical University of Catalonia, Universitat Politècnica de Catalunya (UPC) in September 2010. The aim is to describe the organization, funding and results of a preparatory course in Physics for a bachelor's degree in Engineering. We assess the students' opinions about the experience and whether it should be repeated. We also analyze the profile of the students who access this School, estimating their initial knowledge of physics. The results obtained provide solid evidence that 70% of new students coming from Vocational Education Schools do not meet the required minimums.